Exploring the key success factors: A case study of a digital marketplace platform for Brazilian small farmers - Matos, F.; Catapan, E.; Prado, G.; Zanuzzi, C.; Selig, P. (Procedia Cumputer Science, 2024)
Small agricultural businesses are exposed to global competitive paradigms, and digital marketing platforms have a significant social and economic impact on their competitiveness. An analysis of current product marketplace platforms reveals that many of these platforms cease to exist in an average period of two to three years, which raises the research question: Do any of these platforms have a track record exceeding three years? If so, what are the key success factors that underpin their sustained viability? The objective of this case study is to identify and describe the key success factors of a commercialization platform in Brazil which directly connects small rural producers with their end consumers. Employing an interpretive qualitative approach, this empirical research presents a case study based on a theoretical analysis of the main success factors, examining their application within a Brazilian digital platform facilitating the trade of products between agricultural producers and consumers. The results emphasize key success factors for implementing innovative technology solutions in small agricultural businesses: a committed, supportive management team with visionary leadership; prioritizing market and stakeholder needs; maintaining strong customer relationships; and resource availability. Persistence, resilience, and learning from experiences were also identified as vital skills in the case study, contributing to the platform's long-term success.